Potassium sorbate enhancement of Chlorella sorokiniana cultivation: initial bacterial control and direct growth promotion in piggery wastewater - He-I Lin; Chao-Hsien Lin; Zi-Yan Xu; Tsung-Meng Wu; Pearl Pei-Chun Chang (Current Research in Biotechnology)
Piggery wastewater (PWW) presents environmental challenges due to high nitrogen and phosphorus content yet offers opportunities for sustainable bioenergy production through microalgal cultivation. However, indigenous microorganisms often inhibit microalgal growth during initial establishment phases. This study investigated potassium sorbate (PS) as a novel dual-function additive that provides both transient antimicrobial protection and direct metabolic enhancement for Chlorella sorokiniana T89 cultivation in PWW, distinguishing it from conventional antimicrobial-only strategies. PS effects were compared with sodium hypochlorite (SHC) and untreated controls, monitoring bacterial populations, algal growth, nutrient removal efficiency, and lipid productivity. PS at 1.5 g/L initially reduced bacterial counts by 2 logs, though populations recovered within 24 h. Critically, Chlorella growth enhancement continued despite bacterial recovery, revealing the unique dual mechanism of action that extends beyond the antimicrobial suppression by PS. PS at 1.5 g/L substantially improved nitrogen removal (over 90 % vs. 76 % for SHC and 49 % for controls) and phosphorus removal (over 98 % vs. 87 % for SHC and 72 % for controls), while achieving nearly four-fold higher biomass yield with lipid content exceeding 30 %. Component testing in sterile medium confirmed that sorbic acid, rather than potassium, drove direct metabolic growth promotion, demonstrating the dual role of PS as both an antimicrobial agent and a growth-enhancing substrate. In contrast, SHC showed strong antimicrobial activity but exhibited residual toxicity that inhibited Chlorella growth even under sterile conditions. These findings revealed that PS has dual functionality, providing initial bacterial suppression for successful establishment while simultaneously serving as a metabolic enhancer through sorbic acid. This work demonstrates PS as a promising, low-toxicity alternative for integrated agricultural wastewater treatment and biofuel production systems.